Praktik Lansia Hipertensi dalam Mengendalikan Kesehatan Diri di Wilayah Puskesmas Mranggen Demak - Soesanto, Edy; Istiarti, Tinuk; Pietojo, Harbandinah (Jurnal Promosi Kesehatan Indonesia, 2010)
Hypertension has been defined as the major risk factor of cardiovascular disease in Indonesia. This disease tends to increase along with people’s unhealthy life style, lack of facilities and high service-cost. This study aims to analyze factors influencing hypertension control practice among elderly in Mranggen, Demak. It was a cross sectional study combined quantitative and qualitative method. Total sampling 285 elderly were involved as study objects. Chi-square and logistic regression were employed to analyze the finding. Perceived benefit found to be the strongest predictor of hypertension control practice in this study. Elderly who have better perceived benefit were 3.589 times more likely to have better practice than those who has less perceived benefit. Education, income, daily activities, perceived susceptibility, perceived seriousness, perceived of cost, family support and social support were significantly correlated to hypertension practice in bivariate level.